Pengaruh Kompetensi dan Pengalaman Pengelolaan Barang Milik Daerah terhadap Kualitas Laporan Keuangan Daerah dengan Etika sebagai Variabel Moderasi - Y Sattu, Maris; Sri Hariani, Lilik; Mariani Manik, Yuni (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2025)
This research aims to examine the influence of competence and experience on the quality of regional financial reports with ethics as a moderating variable. This research is quantitative research with a descriptive approach. The population in this study were all employees who worked at the regional financial and asset management agency (BPKAD) of Puncak Jaya district. The data used in the research is primary data collected through a direct questionnaire survey. Data analysis uses multiple linear regression analysis and moderated regression analysis with an absolute difference value approach. Multiple linear regression analysis for competency and experience hypotheses. Multiple linear regression analysis with absolute difference value test for the competency and experience hypothesis moderated by ethics. The results of research using multiple linear regression analysis show that Competence and experience have a positive effect on the quality of regional financial reports. Analysis of moderating variables using the absolute difference value approach shows that ethics is able to moderate competence and experience on the quality of regional financial reports. This means that the better the competence, the more experience and good ethics, the better the quality of regional financial reports in Kolaka Regency.